Ontology of boundaries in contemporary land management: from geometry to regimes of rights and values - Martyn А.; Hunko, L.; Synieutskyi А. (Land Management, Cadastre and Land Monitoring, 2025)
The paper reconceptualizes the boundary in contemporary land management as an institutional–regime category that transcends the geometric view of a dividing line. Drawing on comparative-historical and institutional analysis, deontic modeling, and formal ontologization via LADM, it substantiates a shift from a material-geometric to a regime-based ontology of space, where the boundary operates as an event-relation constituting rights, restrictions, liabilities, and rent flows. Four structural levels—material, legal, informational, and ecological—are identified, and their supervenient couplings are explicated, showing how procedural and data validity causally ground the legitimacy of spatial regimes. The paper formulates principles of boundary ontological design (constitutiveness of procedure, multimodality, adaptability, quality metrics, compatibility and priorities, value transparency) enabling the integration of legal norms, spatial data, and land-value governance mechanisms. Practical relevance includes a transition from a “registry of lines” to a dynamic regime model of space for cadastral and planning systems, improving decision quality, reducing conflicts, and enabling transparent value sharing. The study positions itself as a contribution to the formation of land management theory as a foundational discipline and outlines follow-up work on regime formalization, GeoBIM integration, and legitimacy assessment procedures. Keywords: boundary; spatial ontology; land management; LADM; institutional regimes; rights and restrictions; 3D/4D cadastre; interoperability; value capture; spatial governance.